Pengaruh Harga, Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Di Panganan Waru - Rani Anjariani; Sundjoto Sundjoto; Sri Rahayu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of price, brand image and product quality. This type of research is quantitative. The population studied in this study were all customers at Panganan Waru. The number of samples in this study was 63 respondents. The sample collection technique in this study was carried out by probability sampling. The data collection technique used in this study was a questionnaire distributed to all customers at Panganan Waru. The data analysis technique used in this study was multiple linear regression analysis using SPSS (statistical Product and Services Solution) software version 29.0. The results showed that the price variable had a positive and significant effect on purchasing decisions with a t-count value = 5.809> t-table 2.001, the brand image variable had a positive and significant effect on purchasing decisions with a t-count value = 2.694> t-table 2.001, the product quality variable had a positive and significant effect on purchasing decisions with a t-count value = 3.014> t-table 2.001. From the three results, it shows that price, brand image and product quality have a partial effect on purchasing decisions. For simultaneous testing, the results show that all variables together have a significant effect on purchasing decisions.